2021
DOI: 10.1111/are.15670
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial prophylaxis and molecular docking studies of ketone and ester compounds isolated from Cyperus rotundus L. against Aeromonas veronii

Abstract: Freshwater aquaculture contributes ~55% of the total fish output in India (Dey, Financial Express, 14 February 2020). With the increasing demand for aquatic food products and supply failing to meet the requirements from capture fisheries, the necessity for intensive aquaculture has become apparent (Bueno et al., 2017;Kato &Freitas, 2015;Moffitt & Cajas-Cano, 2014). Despite this, there is still a significant gap between production and commercialization due to mass mortality caused by bacterial diseases (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…These bioactive compounds can attach to particular sites on the toxin and prevent it from building huge complexes that can damage host cells. This kind of in vitro approach is beneficial in decreasing aerolysin toxicity [111]. Our docking studies showed that the key residues of the aerolysin protein's binding pocket, such as Tyr 337, Arg 417, Arg 414, and Tyr 135 interacted with pentanone-5-methoxy via traditional hydrogen bonding and hydrophobic interactions [112].…”
Section: Discussionmentioning
confidence: 91%
“…These bioactive compounds can attach to particular sites on the toxin and prevent it from building huge complexes that can damage host cells. This kind of in vitro approach is beneficial in decreasing aerolysin toxicity [111]. Our docking studies showed that the key residues of the aerolysin protein's binding pocket, such as Tyr 337, Arg 417, Arg 414, and Tyr 135 interacted with pentanone-5-methoxy via traditional hydrogen bonding and hydrophobic interactions [112].…”
Section: Discussionmentioning
confidence: 91%
“…Molecular screening of Patchouli oil ( Pogostemon cablin (Blanco) Benth.) to evaluate the antibacterial activity; [27] antimicrobial efficacy screening of few phytochemical ligands (thymol, carvacrol, and cinnamaldehyde) against Escherichia coli ; [10] antimicrobial screening of compounds isolated from Cyperus rotundus L. against Aeromonas veronii ; [11] molecular screening of essential oil components of Trachyaspermum ammi against the fungal enzyme Candidapepsin‐1; [28] screening out probable inhibitors of trehalose‐6‐phosphate phosphatases of pathogenic microbes from phytochemicals of 5 plant sources ( Aegle marmelos , Ocimum basilicum , Ribes nigrum , Carica papaya and Costus pictus ); [29] to identify some potential drug‐like molecules present in a polyherbal preparation containing Azadirachta indica , Lawsonia alba , and Shorea robusta that can inhibit important drug targets of the dermatophytes [30] were conducted applying biological experimentation and/or molecular docking methods. Molecules based on their binding energy to protein(s) and their concentrations in the extracts were attributed the respective efficacy of a plant extract.…”
Section: Resultsmentioning
confidence: 99%
“…Such studies result in the development of novel drug molecules at a faster pace and reduced cost. In silico molecular docking of phytochemicals for understanding their bioefficacy in disease control including fish diseases is well documented in literature [9–11] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the incorporation of additional nanomaterials, they are more effective and versatile than single-type nanomaterials. Hybrid nanomaterials are created when two or more nanoparticle types are combined, such as carbon-based, metal, or polymeric nanoparticles [ 44 ]. Consequently, as a result of their improved biocompatibility, they are increasingly employed in biological applications such as agriculture, medicine, and medication delivery [ 45 ].…”
Section: Nanomaterials Synthesismentioning
confidence: 99%